PELAYANAN HOME CARE BERBASIS RUMAH SAKIT STUDI KASUS PELAYANAN HOME CARE BERBASIS RUMAH SAKIT SARDJITO YOGYAKARTA TERHADAP LANJUT USIA DENGAN STROKE - Titik Endarwati; I Dewa Putu Pramantara S.; Mubasysyir Hasanbasri (Journal of Health Service Management, 2016)
Background: Home care service that empowers family caregiversenhance the ability, making independent in the care ofpatients at home, reduce or prevent dependence on formalservices. In contrast, business-oriented without empower familycaregivers are part of the hospital health care industrialization.Objective: to describe the characteristics of family caregiver'sindependence caring for elderly in post-stroke at home andempower family caregivers in the services of hospital-basedhome care from the perspective of family caregivers. Methods: This study used a qualitative approach withexploratory case study design. The unit of analysis is theempowerment of family caregivers in the context before dischargefrom the hospital and after at home (home care context)based Sardjito's Hospital. Subjects in this study were 4 familycaregivers, the husband, wife, and children from 3 elderly poststrokepatients Sardjito Hospital. The sampling method used ispurposive sampling. Results: Characteristics of the independence of family caregiversthat have: 1) knowledge of the fulfillment of the needs ofthe elderly ADL; 2) confidence in meeting the needs of theelderly ADL; and 3) the ability to meet the needs of elderly ADL,fix the problem, seek the information needed, utilizing thenurses home visits, and provides tools and materials medical.Educating family caregivers, involving family caregivers inplanning and decision-making, and assured the role of familycaregivers is a strategy to empower family caregivers. Anempowerment strategy done continuously that started at thehospital and continued at home. Conclusions: Family caregiver empowerment strategy inhospital-based home care services increase the independenceof family caregivers in caring for the elderly post-stroke.